Curricular reforms in basic education under three perspectives: common national curricular basis (BNCC), state mediations and music teaching experiences in public schools (Orfeu, 2021)
This paper finality to discuss the difficulties of Music teachers in Basic Education in view of the teaching proposals present in the National Common Curricular Base - BNCC (BRAZIL, 2018). We going to start the arguments of the work from a critical analysis of BNCC, focusing on aspects such as versatility in the area of ​​Art and skills under a market bias. Then, we propose a brief analysis of how state institutions mediate the common base for specific regional contexts, based on the Paranaense Curriculum Reference - RCP (PARANÁ, 2018). Finally, we discuss how teachers deal with curricular proposals, national (BNCC and state (RCP), in the school environment. For that, we take as a basis experiences of teaching and learning in music applied in classes of the final years of the second cycle of Fundamental Education of public schools in London. Based on the analyzes and arguments established in the course of the work, we expect to contribute to discussions regarding curricular parameters that dialogue with the reality of the public school and its teachers, students and the community that integrate them.
Keywords: BNCC; Music teaching; Basic education